A Scoping Review of Research on Mathematical Communication in Indonesia: A Scoping Review of Research on Mathematical Communication in Indonesia - Hanifah; Rahman, Muhammad Syarifuddin (Journal of Research in Science and Mathematics Education, 2024)
Purpose: The objective of this study is to evaluate the development of research on mathematical communication skills in Indonesia through a scoping review approach. Methodology: A total of 271 relevant articles were identified through the use of the DOAJ database. The analysis was conducted based on an examination of publication trends from 2012 to 2024, a review of the journals most frequently utilized, an investigation of the research methods employed, and an analysis of the samples utilized. Findings: The results demonstrated a notable surge in 2022, with 33 articles published, suggesting heightened interest in this subject matter. The journal Axiom represents the primary platform for publications in this field. Mathematical communication is frequently studied from a cognitive perspective, employing qualitative methods and focusing on junior high school students. These findings suggest that there are opportunities to extend research to higher levels of education and to utilize mixed or innovative methods. Significance: A more profound comprehension of mathematical communication skills at higher levels can offer novel perspectives in curriculum development and teaching methodologies. This study recommends an increased integration of technology in mathematics learning and the expansion of the database for future research.